Authoritative Teaching Across Student Populations: The Conflicting Effects of Education and Experience on Elementary Teachers - Torff, Bruce; Murphy, Audrey Figueroa (Journal of Education and Training, 2023)
Elementary-school teachers (N=246) completed a survey to assess the factors that influence teachers’ preferences regarding response, control, and demand, three interactional-style components inherent in “authoritative teaching.” Participants were randomly assigned to answer concerning one of three populations: general-education students, special-education (SPED) students, or English language learners (ELLs). Interactional-style preferences did not differ across student populations and were not associated with teachers’ age or ethnicity. Four factors were associated with significantly higher control scores (gender, educational attainment, certification in SPED, and certification in English as a second language). Teaching experience with all three populations was associated with significantly lower control scores. Teachers take little account of student population in their beliefs about interacting with students, but these beliefs are subject to conflicting forces as their careers proceed, especially concerning classroom management. Targeted professional-development initiatives have potential to help teachers optimize how they interact with students in the classroom.